1991
DOI: 10.1002/bdm.3960040104
|View full text |Cite
|
Sign up to set email alerts
|

Regret and disappointment in taxpayer reporting decisions: An experimental study

Abstract: This paper reports on experiments which test whether factors such as regret or disappointment influence taxpayer compliance decisions. Previous tests of regret and disappointment theory have been based upon the common-ratio effect in which probabilities vary while outcomes are held fixed. In contrast, our experiments involved trials in which the outcomes were allowed to vary. Previous tests had mainly found evidence of regret effects and to a lesser extent were supportive of disappointment. In contrast, we wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…First, in Studies 1 and 2, anticipated regret dealt with a different behavior (failing to play the lottery) than did attitudes, subjective norms, and PBC (playing the lottery). While the original formulation of regret theory stresses the motivational impact of regretting the nonchosen action (e.g., Kelsey & Schepanski, 1991), it is possible that different findings might have been obtained if we had measured anticipated regret with respect to playing the lottery.5 Second, Studies 1 and 2 both concerned intentions to play the lottery, rather than actual behavior. In order to address both of these issues, we conducted a third study.…”
Section: Discussionmentioning
confidence: 98%
“…First, in Studies 1 and 2, anticipated regret dealt with a different behavior (failing to play the lottery) than did attitudes, subjective norms, and PBC (playing the lottery). While the original formulation of regret theory stresses the motivational impact of regretting the nonchosen action (e.g., Kelsey & Schepanski, 1991), it is possible that different findings might have been obtained if we had measured anticipated regret with respect to playing the lottery.5 Second, Studies 1 and 2 both concerned intentions to play the lottery, rather than actual behavior. In order to address both of these issues, we conducted a third study.…”
Section: Discussionmentioning
confidence: 98%
“…Choose poorly and regret it; choose wisely and rejoice. The most common formulation of regret and rejoice is as a result of counterfactual thinking, in which a realized outcome is compared with, "what might have been" (Boles and Messick, 1995;Inman et al, 1997;Kelsey and Schepanski, 1991;Mellers, 2000;Ritov and Baron, 1995;Roese and Olson, 1995;Zeelenberg, 1999). Although a growing body of experimental work supports the existence of the commonsense notions of regret and rejoice, a number of questions remain as to how such a comparative algorithm is implemented both cognitively and neurobiologically in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been suggested that these eects might not be caused by the juxtaposition of the outcomes, but rather by event splitting, increased weighting of consequences when they are split into two subevents than when it is considered as a single event (see, for details, Starmer and Sugden, 1993). Also other research aimed at directly testing predictions from regret theory did not provide unequivocal support (see Harless, 1992;Di Cagnio and Hey, 1988;Kelsey and Schepanski, 1991;Leland, 1998). Despite the mixed success of regret theory, there is some support for the broader claim underlying the theory, that people take regret into account when making decisions.…”
Section: Regret Theorymentioning
confidence: 95%